2023
DOI: 10.9755/ejfa.2023.v35.i6.3098
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional values, Nutraceutical properties, and health benefits of Arabian Date Palme fruit

Abstract: The date palm is widely known as a richer nutritional source and natural medical agent. Date fruit is a major source of carbohydrates and dietary fiber, and it has contains proteins, minerals, vitamins, phenolic compounds, carotenoids, sterols, and triterpenoids. The beneficial potential of this fruit is well known in Arab countries and even in the world. Date fruit has many health benefits such as Glucose-lowering potential, anti-cancer activity, antioxidant activity, hypocholesterolemia-lowering potential, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 138 publications
0
1
0
Order By: Relevance
“…A systematic review of 215 studies highlighted the potential nutritional and pharmaceutical properties of dates, as well as other parts of the palm tree [8]. In Kuwait, researchers [9] examined the biochemical and dietary composition of five varieties of dates. The analysis revealed that the energy content ranged from 3513 to 368.35 kcal/100 g. The potassium content was rich, ranging from 4450 to 7128 mg/100 g, while the calcium content ranged from 287 to 469 mg/100 g. wide range of essential nutrients, including minerals, such as calcium, iron, zinc, and phosphorus, and vitamins such as B complex, D, and A [15].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 215 studies highlighted the potential nutritional and pharmaceutical properties of dates, as well as other parts of the palm tree [8]. In Kuwait, researchers [9] examined the biochemical and dietary composition of five varieties of dates. The analysis revealed that the energy content ranged from 3513 to 368.35 kcal/100 g. The potassium content was rich, ranging from 4450 to 7128 mg/100 g, while the calcium content ranged from 287 to 469 mg/100 g. wide range of essential nutrients, including minerals, such as calcium, iron, zinc, and phosphorus, and vitamins such as B complex, D, and A [15].…”
Section: Introductionmentioning
confidence: 99%